Axial pattern flap in the facial region of a canine: Case report - Freire, Natarsha; de Aguiar Freire, Natarsha; Rebelo Pantoja, André; Neves Linhares, Dejane (Pubvet, 2022)
Reconstructive surgeries aim to seek results in order to benefit animals with trauma to their anatomy, correcting dysfunctions or losses, whether sensory or motor, through the use of flaps, grafts and/or biomaterials; when primary way closing is not possible due to excess tension. The procedure requires technical experience from the professional throughout the process, from the choice of the technique to be used and in the pre- and postoperative follow-up, thus avoiding unnecessary complications or costs. The specific factors to be evaluated start with the location of the lesion and its extension in the animal's body, including bone or tendons, degree of contamination due to exposure time, amount of blood available and finally the amount of skin and elasticity for closing. Thus, the objective of this paper is to describe a report of a reconstructive surgery procedure in axial pattern in the facial region of a canine. The omocervical axial pattern flap proved to be an excellent model for the reconstruction of large defects in the lateral face region. Surgical planning, intraoperative conduct and established postoperative management contributed to a successful postoperative period, with a good recovery of the patient and without complications, currently being a healthy animal.
Keywords: Reconstructive surgeries; quality of life; well-being; trauma